Indentation and scratch testing of DLC-Zr coatings on ultrafine-grained titanium processed by high-pressure torsion - Wang, Chuan Ting (2013)
High-pressure torsion was employed to refine the microstructure of grade 2 Ti under an imposed pressure of 3.0 GPa at room temperature. The microhardness of grade 2 Ti increased from 1.82 GPa for the coarse grain state to 3.05 GPa after high-pressure torsion processing, where this value is very close to the hardness of the Ti–6Al–4V alloy. Subsequently, several diamond-like carbon (DLC) coatings with thicknesses of ∼1.4 μm were deposited on as-received Ti, high-pressure torsion processed Ti and Ti–6Al–4V samples via physical vapour deposition. Both indentation and scratch tests showed a much improved adhesion of DLC-7Zr, DLC:H-7Zr and DLC-9Zr coatings with high-pressure torsion processed Ti as the substrate by comparison with the same coatings on coarse-grained Ti. The results suggest that commercial pure Ti processed by high-pressure torsion and coated with a diamond-like carbon coating provides a potential candidate material for bio-implant applications.